Investigation of Fine Arts High School Music Department Students' Achievement in Quantitative Courses and Their Opinions on These Courses - Döğer, Didem; Gayretli, Şerif (Gazi Üniversitesi, 2019)
In this mixed method research, it is aimed to examine fine arts high school music department students' achievement  in quantitative courses and their opinions about these courses. The sample of the study consists of 48 students in the 9th and 10th grades of Diyarbakır Fine Arts High School Music Department in the 2017-2018 academic year. The quantitative data of the research were obtained by using the students' year-end course grades and the qualitative data were obtained from the answers of the students to 7 open-ended questions including their interests, attitudes, expectations and opinions about quantitative courses. At the end of the study, it was seen that the students were not successful enough in quantitative courses and the achievement scores did not show significant differences in terms of the variables of class and gender. Most of the students had thought that the quantitative courses would be fewer before coming to the fine arts high school, and the majority of them found the weekly time for quantitative courses too much. It was concluded that most of the students had negative attitudes towards quantitative courses, that students with positive attitudes were so because they liked the teacher, and that they did not spend enough time to study quantitative courses. In addition, students stated that quantitative courses are boring, that they do not understand the courses due to lack of basics, and that there should not be courses other than vocational courses in fine arts high school.

Bu karma desenli araştırmada, Güzel Sanatlar Lisesi müzik bölümünde öğrenim görmekte olan öğrencilerin sayısal derslerdeki başarı durumlarının ve bu derslerle ilgili öğrenci görüşlerinin incelenmesi amaçlanmıştır. Araştırmanın örneklemini, 2017-2018 eğitim öğretim yılında, Diyarbakır Güzel Sanatlar Lisesi müzik bölümü 9. ve 10. sınıflarda öğrenim görmekte olan toplamda 48 öğrenci oluşturmaktadır. Araştırmanın nicel verileri, öğrencilerin yılsonu ders notları kullanılarak, nitel verileri ise öğrencilerin sayısal derslerle ilgili ilgi, tutum, beklenti ve görüşlerini içeren 7 adet açık uçlu soruya verdikleri yanıtlardan elde edilmiştir. Araştırmanın sonunda öğrencilerin sayısal derslerde yeterli düzeyde başarılı olamadıkları, başarı puanlarının sınıf ve cinsiyet değişkenine göre anlamlı farklılık göstermediği sonucuna varılmıştır. Öğrencilerin büyük bir kısmı güzel sanatlar lisesine gelmeden önce sayısal derslerin daha az olduğunu düşünmüş olduklarını belirtmiş olup, büyük çoğunluk da sayısal derslerin haftalık ders saatlerini fazla bulmuştur. Öğrencilerin çoğunun sayısal derslere karşı olumsuz tutum sergilediği, olumlu tutum sergileyen öğrencilerin ise ders öğretmenini sevdiği, sayısal derslere çalışmak için ise yeterince zaman ayırmadıkları sonuçlarına ulaşılmıştır. Ayrıca öğrenciler, sayısal derslerin sıkıcı geçtiğini, alt yapı eksikliği nedeniyle dersleri anlamadıklarını ve Güzel Sanatlar Liselerinde mesleki dersler dışında derslerin olmaması gerektiğini belirtmişlerdir.
Güzel Sanatlar Lisesi Müzik Bölümü Öğrencilerinin Sayısal Derslerdeki Başarı Düzeylerinin ve Sayısal Derslere İlişkin Görüşlerinin İncelenmesi
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar